Assessment of the Potential Flood Risk in Sarbaz Drainage Basin - Asadollah Mollazehi; MohammadReza Pudineh; Mahmood Khosravi; Mohsen Armesh; AliAsghar Dehvari (تحقیقات کاربردی علوم جغرافیایی)
Today, due to climate change, natural hazards and how to deal with them are among the most important concerns of researchers in environmental planning and crisis management. The purpose of this study is the assessment of the potential flood risk in Sarbaz drainage basin. For this purpose, the databases including elevation, slope, geological characteristics, soil characteristics, precipitation, vegetation, land use, and vector layers of the main channel, streams and drainage densities of the basin were used. By using the questionnaire and experts' opinion as well as hierarchical analysis, the weight of influences of each layer was calculated in basin flooding. Each of these layers was classified based on the flood potential from low to high-risk scale and eventually merged with the weighted overlay model in Geographic Information System. The results showed that main streams, land use, and precipitation are the most important components in the flood risk of the Sarbaz river drainage basin. From the total area of the Sarbaz basin, only 0.5% has a high to extremely high flood potential, and the central areas of the basin have the highest potential for flood due to topography and special hydrographic conditions. In addition, the main river basin districts towards the outlet of the basin as well as parts of the margins of important sub-streams have the highest flood potential. Despite the limited area of the high-risk zone, due to population density and agricultural land, the importance of this area is very high in crisis management.